A New Concept and Strategy for Photovoltaic and Thermoelectric Power Generation Based on Anisotropic Crystal Facet Unit. (25th May 2020) - Li, Yang; Luo, Kai; Tao, Ran; Wang, Zhiyong; Chen, Daifen; Shao, Zongping
Abstract: According to the classic concept of photovoltaic devices, p–n junctions and heterojunctions are indispensable for carrier separation. Herein, for the first time, a novel concept of "anisotropic crystal facet unit" is put forward and clarified for photovoltaic and thermoelectric power generation. Specifically, an "anisotropic crystal facet unit" in monocrystalline p‐Cu2 O between the {100} and the {111} crystal faces is built, which can fulfill self‐motivated carrier separation, due to their natural energy difference. The "anisotropic crystal facet unit" devices can directly and efficiently convert light and heat into electricity, where the {100} and the {111} faces act as the cathode and the anode, respectively. Moreover, hot and cold regions are unnecessary when the "anisotropic crystal facet unit" is applied in thermoelectric conversion. These findings may update the understanding of solar cells and thermoelectric cells, and blaze a new trail through the development of efficient and low‐cost energy utilization technologies. Abstract : A novel concept of "anisotropic crystal facet unit" is put forward and clarified for photovoltaic and thermoelectric power generation, which can fulfill self‐motivated carrier separation, due to the natural energy difference between the {100} and the {111} crystal faces. The anisotropic crystal facet unit can directly and efficiently convert light and heat into electricity.